Common Arthropod Pests in Blackberries and Pomegranates in Florida - Chastity Perry; Hugh Smith; Zhanao Deng; Sriyanka Lahiri (EDIS)
Blackberry and pomegranate are growing in importance as alternative crops in Florida. In the past decade, blackberry production in Florida increased from 64 acres in 2007 to 173 acres in 2017.  The many health benefits acquired from these fruits make them good alternative options for growers in Florida to diversify their operations by planting some new and less traditional crops, providing them a niche in the Florida agriculture market. The intended audience of this publication includes blackberry and pomegranate growers in Florida as well as Extension agents providing expert recommendations to both these industries. The purpose of this publication is to share information derived from a one-year field survey on commonly encountered pests.